Aspects of the Biology and Culture of the Butterfly Fish, Pantodon buchholzi; A Potential Aquarium Fish in Nigeria - A.T. Ibim; J.O. Ike (Journal of Applied Sciences and Environmental Management)
A review was carried out on a Nigerian fish species with ornamental importance, the Pantodon buchholzi. This was aimed at introducing it an additional aquarium fish and eliciting interest in the large scale culture of the species in Nigeria, to develop the Ornamental Fishery Industry. The study on the biology revealed that the species were spectacular species, possessing unique physical features that confer on them the ornamental status. They are widely distributed in flooded vegetated acidic freshwater environment in Nigeria and some other West African Countries. They require optimum water conditions of 25-27oC, pH of 6.5 -7.0, and hardness of 8-12. The adults are carnivorous, surface hunters, while the juveniles are passive insectivores that prefer live foods, but can be lured into eating fish feed over time. They mature sexually in a year or more. Information on the culture is scarce except for experiences of a few Aquarium fish keepers or hobbyists, who reported that they are hardy, but do not spawn readily in captivity. Also, they are community fishes but can be cannibalistic towards other fishes, and their young too. In conclusion, though the species possesses a great economic potential in the local and International Ornamental fish trade, its culture is not practiced as the species and its economic potentials are not well known, among other constraints.